Penggunaan Media Slime untuk Meningkatkan Motorik Halus Anak Cerebral Palsy di SLB 1 Panti, Pasaman Timur, Padang - Windasari, Windasari; Hasan, Yarmis (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
This study revealed about Cerebral Palsy student in Class 1 at SLB N1 Panti, who had difficulty in holding pencils due to immaturity of muscle strength in fine motoric. This study aims to determine whether the use of slime mediawas effective in improving student's fine motoric. The research method used is classroom action research which consists of II cycles. Each cycle consists of four meetings. Technique of collecting data used are observation, documentation, and tests. From the results of the research in the first cycle the ability of student in squeezing slime was obtained from the results of the first student meeting (46.7%), the second meeting (53.3%), the third meeting (60%), and the fourth meeting (66.7%). The second cycle of student ability in squeezing slime obtained the first meeting results (73.3%), second meeting (80%), third meeting (86.7%), fourth meeting (86.7%). From the results obtained above, it can be seen that the value of students has increased, it can be seen from the ability of student to hold a pencil that was getting better.